Critically Ill Patients in The Emergency Department: Incidence of unconsciousness - Subhan, Nanda (CoinReads Media Prima, 2024)
Introduction: Critically ill or injured patients can be spared the high incidence of decreased awareness of entering an emergency room that is frequently associated with involvement in emergencies. Method: The emergency department (ED) of General Hospital Indonesia was the site of this prospective, observational cohort study. We comprised all consecutive patients admitted to the emergency department from February 15th to March 16th, 2019. Results: Nineteen patients (4.5%) required airway management, while 45 patients (10.7%) necessitated ICU admittance. In total, 422 patients required airway management. The anesthesiology department received 130 emergency patient visits (30.8%) that were referred due to loss of consciousness. In general, this investigation identified 234 non-surgical emergency cases (55.5%) and 188 emergency surgery cases (44.5%). 71 cases (37.8%) of the 130 patients with the most loss of consciousness required emergency surgery. Patients who experience loss of consciousness are at risk for ICU admission, airway management, pain management, and CVC installation, as evidenced by p values (0.001) that are less than 0.05. Conclusion: The prevalence of loss of consciousness was 30.8% (130), and patients experiencing loss of consciousness are risk factors for ICU admission, airway treatment, pain management, and central venous catheter insertion.